Behaviors, attitudes and opinions of medical students in the field of smoking and anti-smoking counseling in two countries of Central and Eastern Europe - Hejda, Paulina; Hubert-Lutecka, Agnieszka; Chmiel, Zdzisława; Sidor, Adam; Iwanowicz-Palus, Grażyna; Żal, Marcin; Koryl, Agnieszka; Binkowska-Bury, Monika (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Europe is the region with the greatest proportion of deaths (16%) attributable to tobacco smoking worldwide. Medical students and physicians should set an example of tobacco-smoking abstinence for their patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to compare opinions on behaviors and attitudes of Czech and Polish medical students about tobacco smoking and the position of a physician in anti-smoking counseling. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The Global Health Professions Student Survey (GHPSS) was conducted among 707 medical students in Czech Republic in 2011 and among 1164 medical students in Poland. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Twety percent of polish and 25,7% of Czech medical students declared current tobacco smoking. Eighty-one percent in Poland and 60% in Czech Republic felt that physicians should be trained in smoking cessation techniques but only 27% of the medical students in Poland and 2,8% in Czech Republic, declared that such a course had been realized during the course of their education. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Over a fifth of Polish students and a quarter of Czech students declared themselves as active smokers. It is worrying that about half of Polish students were exposed to environmental tobacco smoke, while only one-fifth of Czech students declared such exposure. Polish and Czech students agreed that the doctor will play an important role in the patient’s smoking cessation process and that physicians should give advice on quitting smoking.